2012
DOI: 10.2106/jbjs.j.02000
|View full text |Cite
|
Sign up to set email alerts
|

Injury Patterns Causing Isolated Foot Compartment Syndrome

Abstract: Our results demonstrate that injuries involving a crush mechanism, either in isolation or in combination with a forefoot injury, should raise suspicion about the possibility that a foot compartment syndrome will develop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 12 publications
1
25
0
Order By: Relevance
“…Classically, acute compartment syndrome of the foot occurs after high-energy trauma (1) in injuries such as Lisfranc fracture or dislocation, multiple metatarsal fractures, and calcaneal fractures (5). More specifically, foot fractures caused by crush injuries increase the likelihood of compartment syndrome (2). In 1 study, one third of the patients identified who had undergone fasciotomy had had isolated forefoot injuries (2).…”
Section: Discussionmentioning
confidence: 99%
“…Classically, acute compartment syndrome of the foot occurs after high-energy trauma (1) in injuries such as Lisfranc fracture or dislocation, multiple metatarsal fractures, and calcaneal fractures (5). More specifically, foot fractures caused by crush injuries increase the likelihood of compartment syndrome (2). In 1 study, one third of the patients identified who had undergone fasciotomy had had isolated forefoot injuries (2).…”
Section: Discussionmentioning
confidence: 99%
“…Few epidemiological studies report the incidence of FCS in foot and ankle injuries and therefore the numbers in the literature differ considerably. A FCS is seen in up to 20% in Lisfranc-fracturedislocations and up to 10% of calcaneal fractures [1,30,32,34,37,40]. Many of these are combined or complex injuries to the foot (e. g. combined Chopart-and Lisfranc fracture-dislocations) while isolated fractures less frequently appear to lead to a FCS.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the latter patient population may be undertreated and the diagnosis missed in a considerable amount of patients [5]. A recent study showed a 2% incidence of FCS in isolated foot injuries [40]. With complex trauma of the footan entity defined as multilevel fractures with high degree soft tissue damage [2,43] -the incidence of FCS rises to more than 50% [17,39].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the reported ten percent incidence of compartment syndrome historically associated with calcaneus fractures [28] may no longer be considered accurate. The highest incidence of foot compartment syndrome was seen in association with crush injuries and forefoot injuries [27].…”
mentioning
confidence: 99%
“…Fulkerson et al noted that until the 1980s foot compartment syndrome was largely unrecognised [26]. In their series of 364 patients with an isolated foot compartment syndrome, Thakur et al found that only 1% of 2481 patients with an isolated calcaneal fracture underwent fasciotomy [27]. Therefore, the reported ten percent incidence of compartment syndrome historically associated with calcaneus fractures [28] may no longer be considered accurate.…”
mentioning
confidence: 99%